2010
DOI: 10.1016/j.jcin.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Improved Late Clinical Safety With Zotarolimus-Eluting Stents Compared With Paclitaxel-Eluting Stents in Patients With De Novo Coronary Lesions

Abstract: Three-year follow-up results from the ENDEAVOR IV trial indicate similar antirestenosis efficacy but improved clinical safety associated with ZES compared with PES, due to significantly fewer peri-procedural and remote MIs associated with fewer VLST events. (A Randomized, Controlled Trial of the Medtronic Endeavor Drug [ABT-578] Eluting Coronary Stent System Versus the Taxus Paclitaxel-Eluting Coronary Stent System in De Novo Native Coronary Artery Lesions; NCT00217269).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(22 citation statements)
references
References 24 publications
(14 reference statements)
1
21
0
Order By: Relevance
“…After the first ENDEAVOR trials, the subsequent ENDEAVOR III trial compared ZESs with SESs, with ZES showing greater late lumen loss and ISR but less major adverse cardiovascular events (MACE) than SESs 30. The ENDEAVOR IV trial compared ZESs with PESs and again found higher rates of ISR but fewer AMIs, ostensibly from very late ST in the ZES group 31. However, the PROTECT trial failed to demonstrate a difference in ST rates between Endeavor and Cypher stent 32…”
Section: Coronary Stentsmentioning
confidence: 99%
“…After the first ENDEAVOR trials, the subsequent ENDEAVOR III trial compared ZESs with SESs, with ZES showing greater late lumen loss and ISR but less major adverse cardiovascular events (MACE) than SESs 30. The ENDEAVOR IV trial compared ZESs with PESs and again found higher rates of ISR but fewer AMIs, ostensibly from very late ST in the ZES group 31. However, the PROTECT trial failed to demonstrate a difference in ST rates between Endeavor and Cypher stent 32…”
Section: Coronary Stentsmentioning
confidence: 99%
“…Recent studies have shown that second-generation DESs (Everolimus-eluting or Zotarolimuseluting stent) lead to more favorable healing profiles18) and are associated with lower rates of ST compared with first-generation DESs 19)20)…”
Section: Discussionmentioning
confidence: 99%
“…ENDEAVOR IV (Randomized Comparison of Zotarolimus and Paclitaxel-Eluting Stents in Patient with Coronary Artery Disease) showed noninferiority of the ZES to the paclitaxel-eluting stent (PES) for target vessel failure (cardiac death, MI, target vessel revascularization) at 9-month follow-up 43. Long-term follow-up found similar rates of target lesion revascularization (6.5% versus 6.1%, P =0.662) with an improvement in rates of cardiac death, MI, and very late stent thrombosis, (0.1% versus 1.6%, P =0.004), favoring the Endeavor 44. However, when the ZES was compared with the sirolimus-eluting stent (SES) in ENDEAVOR III (Comparison of Zotarolimus-Eluting and Sirolimus-Eluting stents in Patients With Native Coronary Artery Disease), the results were not as convincing regarding its improvement over first-generation DES 45.…”
Section: Stent Evolution In Clinical Trialsmentioning
confidence: 99%